Comunicação por imagens e produção de conhecimento: O Vento nos Levará , de Abbas Kiarostami - Gauche, Renata Monastirscy (2012)
This research aims to understand how the production of knowledge occurs through a communication by images, where the object of exemplifying the film "The Wind Will Carry Us" by Abbas Kiarostami. The question that motivates the research is that the film productions that explore a mass communication technique used to request less the imagination of the subject. Abbas Kiarostami, in "The Wind Will Carry Us", proposes a new cinematic language that encourages the "see no show", which comes against the current molds imposed by classical Hollywood film, a film exploring "stretch the neck." In the search for an understanding of how this film as a film set, through a new cinematic language that breaks with the narrative structure, we try to understand the production of knowledge through images made critical, always about to be born. Having as a research methodology to analyze the semiotics of film setting, linked to the theoretical basis required by the object of study, the research is based on the following assumptions: 1) by means of a new language Kiarostami seeks other ways to involve the viewer and view / Read the territory, the culture of your country, 2) Kiarostami does not propose a narrative, in which images have a story to tell, but it occupies an opening narrative forms in training, in other words, there is no narrative in the film, and therefore there is entertainment, 3) communication through images, through dialectical images, boosts the functioning of the imagination and knowledge production. The theoretical basis of this study is the concept that man thinks and communicates through images, through studies of Belting, Flusser, Bachelard and Calvin. To understand the language of Kiarostami and how it deconstructs the film, will support research on concepts developed by Kiarostami, Bernardet, beyond the concepts of visuality, visibility and dialectics, developed by Benjamin, Didi-Huberman, Sodré, Ferrara and Flusser, requested to understand the communication flow as it expands and contracts in a process of endless change